Ewing sarcoma of distal phalanx of the great toe in a 10-year-old boy: case report and review of the literature - Peeters, S.; Van Laethem, A.; Sciot, R.; Renard, M.; Labarque, V.; Vanden Bempt, I.; Verhamme, B. (European Journal of Pediatric Dermatology, 2025)
Ewing sarcoma (ES) is a malignant tumor that arises in bone or soft tissue, and usually affects the pelvis and proximal long bones, although it can occur in any part of the body. ES of the foot is extremely rare, and its clinical presentation can mimic that of more common diseases. We present a case of ES of the distal phalanx of the great toe in a 10-year-old boy. Only 12 cases involving the toes have been reported in the literature, with only 4 affecting the distal phalanges. This case is a valuable addition to the literature and highlights the importance of including ES in the differential diagnosis to minimize delay in diagnosis.